Coated cloth with Chinese art paper wetting effect

By forming an esterification layer on the polyester plain weave fabric base layer and using the esterification reaction of oxidized starch and citric acid, the problem of weak bonding strength between the polyester plain weave fabric base material and the slurry is solved, achieving efficient bonding and good wetting effect, which is close to the use performance of rice paper.

CN119711200AActive Publication Date: 2025-03-28WUXI PHOENIX ARTIST MATERIALS

Patent Information

Application Number
CN202510213783.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

In the prior art, when using polyester plain fabric as a substrate to create a coating cloth with a wetting effect in rice paper, the bonding force between the slurry and the substrate is weak, making it difficult to meet the demand for efficient bonding.

Method used

By forming an esterification layer on the polyester plain weave fabric base layer, the esterification reaction of oxidized starch and citric acid is used to closely combine it in the surface of the substrate and the weft and line gaps, and is formed integrally with the scraped slurry to enhance the binding force between the slurry and the substrate.

Benefits of technology

The bonding force between the coating cloth and the slurry is significantly improved, and the wetting effect of the coating cloth is enhanced, making it closer to the use performance of rice paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711200A_ABST
    Figure CN119711200A_ABST
Patent Text Reader

Abstract

The invention provides coated cloth with a Chinese art paper wetting effect, the coated cloth comprises a polyester plain weave fabric base layer, an esterification layer and a blade coating slurry layer, the esterification layer is tightly combined on the upper surface of the polyester plain weave fabric base layer and in gaps of polyester warps and wefts, and the blade coating slurry layer and the esterification layer are integrally formed; wherein the blade coating slurry layer mainly comprises oxidized starch and carboxylated nanocellulose, and the hydroxyl functional group content of the oxidized starch in the blade coating slurry layer is greater than the carboxyl functional group content of the carboxylated nanocellulose; the esterification layer is formed by esterification reaction between surplus hydroxyl functional groups of oxidized starch and citric acid dip-coated on the surface of the polyester plain weave fabric base layer. According to the invention, citric acid is used as a medium and reacts with surplus hydroxyl in the blade coating slurry to generate an esterification layer, so that the binding force between the blade coating slurry and the polyester plain weave fabric base layer is better; and the anhydrous citric acid can absorb water to obtain hydrate, so that the wetting effect of the coated fabric is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of canvas, in particular to a coated cloth with rice paper wetting effect. Background Art

[0002] Canvas painting is usually only used in the field of Western oil painting, while Chinese ink painting can only be done on rice paper. The traditional production process of rice paper has very high requirements for the process environment, climate, temperature, and operator skills, which makes it difficult to sustain the output of rice paper. In addition, the market price of high-quality rice paper is high, and the purchase and use costs of ordinary painters are also high.

[0003] The applicant has applied for multiple patents for canvas with rice paper effect, such as: a rice paper-like coating and rice paper-like coating, preparation method and application thereof disclosed in patent publication number CN117738024A, a preparation method of hand-painted canvas imitating rice paper penetration disclosed in patent application publication number CN115341381A, and an ink-absorbing and drying canvas disclosed in patent announcement number CN103741481B. However, the research and development of this technology in China is limited, and there are still some problems. For example, a filler (cellulose fiber, nano calcium carbonate, etc.) and a sizing agent (starch, modified starch, etc.) are combined and scraped on the surface of the fabric. However, when combined with a chemical fiber material substrate such as polyester, the bonding strength between the sizing agent and polyester still has room for improvement. Summary of the invention

[0004] The technical problem to be solved by the embodiments of the present invention is to provide a coated cloth with a rice paper wetting effect, and solve the problem that the coated cloth with a rice paper wetting effect made of polyester plain weave fabric as a substrate has weak bonding strength with slurry.

[0005] In order to solve the above technical problems, the present invention provides a coated cloth with a rice paper wetting effect, comprising a polyester plain weave fabric base, an esterification layer and a scraping slurry layer, wherein the esterification layer is tightly combined with the upper surface of the polyester plain weave fabric base and the gaps between the polyester warp and weft lines, and the scraping slurry layer and the esterification layer are integrally formed; wherein the scraping slurry layer is mainly composed of oxidized starch and carboxylated nanocellulose, wherein the oxidized starch and the carboxylated nanocellulose are prepared in a weight ratio of (3-20):1, and the hydroxyl functional group content of the oxidized starch in the scraping slurry layer is greater than the carboxyl functional group content of the carboxylated nanocellulose, and the esterification layer is formed by an esterification reaction between the surplus hydroxyl functional groups of the oxidized starch and the citric acid dip-coated on the surface of the polyester plain weave fabric base.

[0006] The thickness of the polyester plain weave fabric base layer is 0.3-0.6mm; the average thickness of the scraped slurry layer is between 0.1-0.2mm; the thickness of the esterification layer on the upper surface of the polyester plain weave fabric base layer is between 0.02-0.05mm, and the depth of the esterification layer sinking into the gaps between the polyester warp and weft lines is between 0.2-0.4mm; wherein, the formation of the esterification layer is that the polyester plain weave fabric base layer is firstly dipped in a citric acid solution, and then the slurry coated on the polyester plain weave fabric base layer is infiltrated into the gaps between the warp and weft lines of the polyester plain weave fabric base layer by wind force, and the oxidized starch in the slurry and the citric acid are heated to produce an esterification reaction.

[0007] The citric acid is obtained by immersing the polyester plain weave fabric base into a citric acid solution before applying the slurry, or spraying the citric acid solution onto the upper surface of the polyester plain weave fabric base. The citric acid content in the citric acid solution is 3-5wt%.

[0008] Before applying the slurry, hot air needs to be blown toward the lower surface of the polyester plain weave fabric base layer to evaporate the water in the citric acid solution and keep the citric acid on the upper surface of the polyester plain weave fabric base layer and in the gaps between the polyester warp and weft lines.

[0009] The temperature of the hot air is between 60-75°C to avoid decomposing the citric acid hydrate.

[0010] In the doctor blade coating slurry, the weight of the oxidized starch and the carboxylated nanocellulose does not exceed 10% of the total weight.

[0011] The scraping slurry also includes 0.5wt% of a water-based polyurethane thickener, 0.02wt% of an isothiazolinone preservative, 0.2wt% of a leveling agent, 0.15wt% of a dispersant and 0.15wt% of a defoaming agent.

[0012] The slurry preparation process of scraper coating includes: preparing an oxidized starch solution and gelatinizing the oxidized starch solution; preparing a carboxylated nanocellulose dispersion; The gelatinized oxidized starch solution and the carboxylated nanocellulose dispersion were mixed in a mass ratio of 2:8, and then mixed evenly by magnetic stirring.

[0013] The carboxylated nanocellulose is prepared by Acetobacter xylinum and then subjected to a carboxylation reaction.

[0014] The preparation process of the carboxylated nanocellulose comprises: (i) Acetobacter xylinum produces nanocellulose through biosynthesis; 1. Culture conditions Culture medium: Commonly used HS culture medium (containing glucose, yeast extract, peptone, phosphate, etc.) provides carbon and nitrogen sources.

[0015] Training method: The bacterial dispersion is promoted by a stirred or airlift reactor to produce granular cellulose.

[0016] Culture period: usually 5-7 days, temperature 28-30°C, pH 4.5-6.0.

[0017] 2. Synthesis mechanism of nanocellulose Acetobacter xylinum polymerizes glucose into β-1,4-glucan chains through the cellulose synthase complex on the cell membrane.

[0018] Multiple glucan chains self-assemble into nanofibers (3-50 nm in diameter) through hydrogen bonds, forming a three-dimensional network structure.

[0019] 3. Post-processing Purification: remove bacteria and culture medium residues, common steps: Alkali treatment (0.1-1 M NaOH, 80°C, 1-2 h) solubilizes bacterial proteins.

[0020] Wash repeatedly until neutral.

[0021] Mechanical homogenization or sonication disperses the nanofibers.

[0022] (ii) Carboxylation reaction of nanocellulose: chemical grafting; The chemical grafting includes: introducing carboxylic acid groups by esterification or etherification reaction (such as reaction with maleic anhydride).

[0023] The aspect ratio of the carboxylated nanocellulose is between 25 and 100, wherein the diameter is 10 to 20 nm and the length is 0.5 to 1 μm.

[0024] After the slurry is scraped onto the upper surface of the polyester plain fabric base, hot air at a temperature of 60-75°C is blown vertically onto the slurry on the polyester plain fabric base, so that the slurry is subjected to the pressure of the hot air, and a part of the slurry enters the gaps between the warp and weft lines of the polyester plain fabric base; After the slurry is dried and the esterification reaction between the surplus hydroxyl groups in the slurry and the carboxyl groups of citric acid is sufficient to form an esterification layer, hot air at a temperature of 78-90°C is blown upward from the lower surface of the polyester plain fabric base layer to decompose the remaining citric acid hydrate to obtain anhydrate.

[0025] The coated cloth with rice paper wetting effect provided by the present invention uses citric acid as a medium to react with surplus hydroxyl groups in the scraping slurry to form an esterification layer, thereby improving the bonding strength between the scraping slurry and the polyester plain weave fabric base layer; and the anhydrate of citric acid can also absorb water to obtain a hydrate, thereby improving the wetting effect of the coated cloth. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the planar structure of the polyester plain weave fabric base layer (the size ratio of the gap and the warp and weft lines shown in the figure is not the real ratio, the actual gap is very small, and the gap is enlarged for explanation).

[0027] Figure 2 Schematic diagram of the cross-sectional structure of the polyester plain weave fabric base layer.

[0028] Figure 3 Schematic diagram of the layered structure of the coated cloth with rice paper wetting effect.

[0029] Figure 4 Schematic diagram of the layered structure of the coated cloth with rice paper wetting effect (with Figure 3 The cutting position is different).

[0030] Figure 5 This is an electron microscope photo of the coated cloth with the wetting effect of rice paper (the picture shows the random distribution of linear carboxylated nanocellulose).

[0031] Figure 6 This is an electron microscope photo of the green pigment soaked in the coated cloth with the wetting effect of rice paper.

[0032] Figure 7 This is an electron microscope photograph of the red pigment soaked in the coated cloth with the wetting effect of rice paper.

[0033] Figure 8 This is an electron microscope photograph of the coated cloth with the wetting effect of rice paper and the infiltrated black pigment.

[0034] Fig. 9 This is an electron microscope photo of the red stripe wetting effect of the coated cloth with the wetting effect of rice paper.

[0035] In the figure: 1- polyester plain weave fabric base layer, 2- esterification layer, 3- scraping slurry layer; 11- warp, 12- weft, 13- gap. DETAILED DESCRIPTION

[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0037] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0039] Combination Figure 1-9 As shown, the present invention provides a coated cloth with a rice paper wetting effect, comprising a polyester plain weave fabric base 1, an esterification layer 2 and a scraping slurry layer 3, wherein the esterification layer 2 is tightly combined with the upper surface of the polyester plain weave fabric base 1 and the gap 13 of the polyester warp and weft lines, and the scraping slurry layer 3 is integrally formed with the esterification layer 2; wherein the scraping slurry layer 3 is mainly composed of oxidized starch and carboxylated nanocellulose, wherein the oxidized starch and the carboxylated nanocellulose are prepared in a weight ratio of (3-20):1, and the scraping slurry layer The hydroxyl functional group content of the oxidized starch is greater than the carboxyl functional group content of the carboxylated nanocellulose, and the esterified layer 2 is formed by an esterification reaction between the surplus hydroxyl functional groups of the oxidized starch and the citric acid dipped on the surface of the polyester plain fabric base layer 1, that is, the esterified layer 2 is formed by the esterification reaction between the surplus hydroxyl functional groups of the oxidized starch and the citric acid dipped on the surface of the polyester plain fabric base layer 1, that is, the esterified layer 2 is formed by the oxidized starch in the scraped slurry contacting the polyester plain fabric base layer 1 after the scraped slurry layer 3 is scraped on the polyester plain fabric base layer, and then the esterification reaction occurs with the citric acid attached to the polyester plain fabric base layer at a suitable temperature (for example, about 60°C). The citric acid is formed by the polyester plain fabric base layer 1 being immersed in the citric acid solution, so that the citric acid solution is attached to the polyester plain fabric base layer, and then the citric acid solution on the polyester plain fabric base layer is dried at a certain temperature, for example, by hot air below 60°C, to ensure that the citric acid does not undergo a decomposition reaction, thereby increasing the concentration of the residual citric acid solution, so as to facilitate contact with the scraped slurry and combined reaction.

[0040] The thickness of the polyester plain fabric base layer is 0.3-0.6mm; the average thickness of the scraped slurry layer is between 0.1-0.2mm, and the maximum thickness of the scraped slurry layer can reach 0.3mm; the thickness of the esterification layer on the upper surface of the polyester plain fabric base layer is between 0.02-0.05mm, and the depth of the esterification layer sinking into the gaps between the polyester warp and weft lines is between 0.2-0.4mm. This sinking depth is very important, and it can greatly increase the bonding force between the polyester plain fabric base layer 1 and the slurry on it. The formation of the esterification layer is that the polyester plain fabric base layer is first dipped in a citric acid solution, and then the slurry coated on the polyester plain fabric base layer is penetrated into the gaps between the warp and weft lines of the polyester plain fabric base layer by wind power, and the oxidized starch in the slurry and the citric acid are heated to produce an esterification reaction.

[0041] The citric acid is obtained by immersing the polyester plain weave fabric base into a citric acid solution before applying the slurry, or spraying the citric acid solution onto the upper surface of the polyester plain weave fabric base. The citric acid content in the citric acid solution is 3-5wt%.

[0042] Before scraping the slurry, it is necessary to blow hot air to the lower surface of the polyester plain fabric base 1 to evaporate the water in the citric acid solution and keep the citric acid on the upper surface of the polyester plain fabric base and the gaps between the polyester warp and weft lines. The function of blowing hot air to the lower surface of the polyester plain fabric base 1 is to blow the citric acid solution from bottom to top, so that more of the citric acid solution moves to the upper surface of the polyester plain fabric base 1, and the upper surface of the polyester plain fabric base acts as a scraping surface and contacts the slurry, so that the citric acid can contact the slurry more fully and react fully to obtain better bonding with the slurry.

[0043] The temperature of the hot air is between 60-75°C to avoid decomposing the citric acid hydrate; since the hydrate in the citric acid solution will begin to decompose when the temperature exceeds 78°C, it is necessary to avoid the decomposition of the citric acid hydrate into anhydrate when heating and evaporating the citric acid. In the doctor blade slurry, the weight of oxidized starch and carboxylated nanocellulose does not exceed 10% of the total weight, and is preferably 1%-1.5%.

[0044] The coating slurry also contains 0.5wt% of water-based polyurethane thickener, 0.02wt% of isothiazolinone preservative, 0.2wt% of leveling agent, 0.15wt% of dispersant and 0.15wt% of defoamer. These additives can be added in the process of mixing the oxidized starch with the carboxylated nanocellulose dispersion after gelatinization, and the mixture should be fully stirred and mixed.

[0045] The slurry preparation process of scraper coating includes: An oxidized starch solution is prepared and gelatinized; specifically, nano starch is modified to obtain oxidized starch, and then the oxidized starch and pure water are mixed and stirred evenly, and then heated to 62-68° C., so as to gelatinize the oxidized starch; Prepare a carboxylated nanocellulose dispersion; specifically, mix the carboxylated nanocellulose with pure water, and then stir evenly to form a dispersion; The gelatinized oxidized starch solution and the carboxylated nanocellulose dispersion are mixed in a mass ratio of 2:8, and then additives such as thickener, preservative, leveling agent, dispersant, defoaming agent, etc. are added, and then mixed evenly by magnetic stirring.

[0046] The carboxylated nanocellulose is prepared by Acetobacter xylinum and then subjected to a carboxylation reaction, and the carboxyl content of the surface of the nanocellulose is 1.5-2.5 mmol / g.

[0047] The preparation process of the carboxylated nanocellulose comprises: (i) Acetobacter xylinum produces nanocellulose through biosynthesis; 1. Culture conditions Culture medium: Commonly used HS culture medium (containing glucose, yeast extract, peptone, phosphate, etc.) provides carbon and nitrogen sources.

[0048] Training method: The bacterial dispersion is promoted by a stirred or airlift reactor to produce granular cellulose.

[0049] Culture period: usually 5-7 days, temperature 28-30°C, pH 4.5-6.0.

[0050] 2. Synthesis mechanism of nanocellulose Acetobacter xylinum polymerizes glucose into β-1,4-glucan chains through the cellulose synthase complex on the cell membrane.

[0051] Multiple glucan chains self-assemble into nanofibers (3-50 nm in diameter) through hydrogen bonds, forming a three-dimensional network structure.

[0052] 3. Post-processing Purification: remove bacteria and culture medium residues, common steps: Alkali treatment (0.1-1 M NaOH, 80°C, 1-2 h) solubilizes bacterial proteins.

[0053] Wash repeatedly until neutral.

[0054] Mechanical homogenization or sonication disperses the nanofibers.

[0055] (ii) Carboxylation reaction of nanocellulose: chemical grafting; The chemical grafting includes: introducing carboxylic acid groups by esterification or etherification reaction (such as reaction with maleic anhydride).

[0056] The aspect ratio of the carboxylated nanocellulose is between 25 and 100, wherein the diameter is 10 to 20 nm and the length is 0.5 to 1 μm.

[0057] After the slurry is scraped onto the upper surface of the polyester plain fabric base, hot air at a temperature of 60-75°C is blown vertically onto the slurry on the polyester plain fabric base, so that the slurry is subjected to the pressure of the hot air, and a part of the slurry enters the gaps between the warp and weft lines of the polyester plain fabric base; After the slurry is dried and the esterification reaction between the surplus hydroxyl groups in the slurry and the carboxyl groups of citric acid is sufficient to form an esterification layer, hot air with a temperature of 78-90°C is blown upward from the lower surface of the polyester plain weave fabric base layer to decompose the remaining citric acid hydrate to obtain anhydrate. Because citric acid will decompose into water vapor and carbon dioxide when the temperature exceeds 90°C. Citric acid is slightly deliquescent in humid air and can exist in the form of anhydrate or monohydrate. It will decompose to obtain anhydrate when heated to 78°C. Therefore, the hot air temperature is controlled to exceed 78°C but not exceed 90°C. The purpose is to promote the decomposition of citric acid into anhydrate, but to avoid further decomposition into water vapor and carbon dioxide due to excessive temperature. By retaining the effective ingredients of citric acid and making it exist in the form of anhydrate, it can play a hygroscopic role after the coated cloth is formed, so that the wetting effect of the coated cloth is better.

[0058] The coated cloth with rice paper wetting effect provided by the present invention uses citric acid as a medium to react with surplus hydroxyl groups in the scraping slurry to form an esterification layer, thereby improving the bonding strength between the scraping slurry and the polyester plain weave fabric base layer; and the anhydrate of citric acid can also absorb water to obtain a hydrate, thereby improving the wetting effect of the coated cloth.

[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A coated cloth having a rice paper wetting effect, characterized in that: The invention comprises a polyester plain weave fabric base layer, an esterification layer and a scraping slurry layer, wherein the esterification layer is tightly combined with the upper surface of the polyester plain weave fabric base layer and the gaps between the polyester warp and weft lines, and the scraping slurry layer and the esterification layer are integrally formed; wherein the scraping slurry layer is mainly composed of oxidized starch and carboxylated nanocellulose, wherein the oxidized starch and the carboxylated nanocellulose are prepared in a weight ratio of (3-20):1, and the hydroxyl functional group content of the oxidized starch in the scraping slurry layer is greater than the carboxyl functional group content of the carboxylated nanocellulose, and the esterification layer is formed by an esterification reaction between the surplus hydroxyl functional groups of the oxidized starch and citric acid dip-coated on the surface of the polyester plain weave fabric base layer.

2. The coated cloth according to claim 1, characterized in that: The thickness of the polyester plain weave fabric base layer is 0.3-0.6mm; the average thickness of the scraped slurry layer is between 0.1-0.2mm; the thickness of the esterification layer on the upper surface of the polyester plain weave fabric base layer is between 0.02-0.05mm, and the depth of the esterification layer sinking into the gaps between the polyester warp and weft lines is between 0.2-0.4mm; wherein, the formation of the esterification layer is that the polyester plain weave fabric base layer is first dipped in a citric acid solution, and then the slurry coated on the polyester plain weave fabric base layer is penetrated into the gaps between the warp and weft lines of the polyester plain weave fabric base layer by wind force, and the oxidized starch in the slurry and the citric acid are heated to produce an esterification reaction.

3. The coated cloth according to claim 1, characterized in that: The citric acid is obtained by immersing the polyester plain weave fabric base layer in a citric acid solution before applying the slurry, or by spraying the citric acid solution onto the upper surface of the polyester plain weave fabric base layer; the citric acid content in the citric acid solution is 3-5wt%.

4. The coated cloth according to claim 1, characterized in that: Before applying the slurry, hot air needs to be blown toward the lower surface of the polyester plain weave fabric base layer to evaporate the water in the citric acid solution and keep the citric acid on the upper surface of the polyester plain weave fabric base layer and in the gaps between the polyester warp and weft lines.

5. The coated cloth according to claim 4, characterized in that: The temperature of the hot air is between 60-75°C to avoid decomposing the citric acid hydrate.

6. The coated cloth according to claim 1, characterized in that: In the doctor blade coating slurry, the weight of the oxidized starch and the carboxylated nanocellulose does not exceed 10% of the total weight.

7. The coated cloth according to claim 6, characterized in that: The scraping slurry also includes 0.5wt% of a water-based polyurethane thickener, 0.02wt% of an isothiazolinone preservative, 0.2wt% of a leveling agent, 0.15wt% of a dispersant and 0.15wt% of a defoaming agent.

8. The coated cloth according to claim 1, characterized in that: The slurry preparation process of scraper coating includes: preparing an oxidized starch solution and gelatinizing the oxidized starch solution; preparing a carboxylated nanocellulose dispersion; The gelatinized oxidized starch solution and the carboxylated nanocellulose dispersion were mixed in a mass ratio of 2:8, and then mixed evenly by magnetic stirring.

9. The coated cloth according to claim 8, characterized in that: The carboxylated nanocellulose is prepared by Acetobacter xylinum and then subjected to a carboxylation reaction.

10. The coated cloth according to claim 8, characterized in that: The aspect ratio of the carboxylated nanocellulose is between 25 and 100, wherein the diameter is 10 to 20 nm and the length is 0.5 to 1 μm.

11. The coated cloth according to claim 8, characterized in that: After the slurry is scraped onto the upper surface of the polyester plain fabric base, hot air at a temperature of 60-75°C is blown vertically onto the slurry on the polyester plain fabric base, so that the slurry is subjected to the pressure of the hot air, and a part of the slurry enters the gaps between the warp and weft lines of the polyester plain fabric base; After the slurry is dried and the esterification reaction between the surplus hydroxyl groups in the slurry and the carboxyl groups of citric acid is sufficient to form an esterification layer, hot air at a temperature of 78-90°C is blown upward from the lower surface of the polyester plain fabric base layer to decompose the remaining citric acid hydrate to obtain anhydrate.

Citation Information

Patent Citations

  • A type of ink-absorbing, stand-drying canvas

    CN103741481B

  • Preparation method of imitation Xuan paper permeation hand-painted cloth

    CN115341381A

  • Waterproof exsiccative breathable synthetic leather and cleaner production method thereof

    CN104928944A

  • Environment-friendly treatment method for reducing shrinkage rate of elastic fabric and elastic fabric

    CN114875682A

  • Chinese art paper-like coating, Chinese art paper-like coating, preparation method and application of Chinese art paper-like coating

    CN117738024A

Cited By

  • Coated fabric having wetting effect of xuan paper

    WO2026180000A1